Protein Arginine Methyltransferase 1 Methylates Smurf2 - Cha, Boksik (Mol Cells, 2015)
Smurf2, a member of the HECT domain E3 ligase family, is well known for its role as a negative regulator of TGF-β signaling by targeting Smads and TGF-β receptor. However, the regulatory mechanism of Smurf2 has not been elucidated. Arginine methylation is a type of post-translational modification that produces monomethylated or dimethylated arginine residues. In this report, we demonstrated methylation of Smurf2 by PRMT1. In vitro methylation assay showed that Smurf2, not Smurf1, was methylated by PRMT1. Among the type I PRMT family, only PRMT1 showed activity for Smurf2. Transiently expressed Smurf2 was methylated by PRMT1, indicating Smurf2 is a novel substrate of PRMT1. Using deletion constructs, methylation sites were shown to be located within amino acid region 224–298 of Smurf2. In vitro methylation assay following point mutation of putative methylation sites confirmed the presence of Arg232, Arg234, Arg237, and Arg239. Knockdown of PRMT1 resulted in increased Smurf2 expression as well as inhibition of TGF-β-mediated reporter activity. Although it is unclear whether or not increased Smurf2 expression can be directly attributed to lack of methylation of arginine residues, our results suggest that methylation by PRMT1 may regulate Smurf2 stability and control TGF-β signaling.